COOPERATION BETWEEN THE FAMILY AND THE EDUCATIONAL SYSTEM IN BRINGING UP THE NEW GENERATION - Aidarbekova, R.K.; Kuatova, А.А. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
The article describes the place of the family and education in raising a generation. It connects the ideas of Kazakh folk literature about raising a generation with today's pedagogy.
Keywords: school–family relations; school–parent relations; extracurricular activities; generation; child rearing